EVALUATION OF FARMERS APPRECIATION IN REDUCING PESTICIDE BY ORGANIC FARMING PRACTICE - ., Indraningsih; Sani, Yulvian; Widiastuti, Raphaella (Indonesian Journal of Agricultural Science, 2005)
Vegetables and dairy milk are important commodities in Pangalenganand Lembang, West Java. However, agrochemicals areused intensively and excessively in production system. Therefore,pesticide residues and contamination commonly occurredin agricultural products and environments. The study aimed toassess farmersâ attitudes on pesticide toxicity and reducingpesticide residues in animal and food crops products, andinvestigate the attitude changes of farmers on pesticide use. Itwas an on-farm research and farmers were directly involved inthe study. The attitude change was analyzed on questionnaireand interview base for over 99 respondents in Pangalengan andLembang between 2001 and 2003. Samples of soils, weeds,cabbages and milk were collected for pesticide residue analysis.Results showed that farmers did not aware on toxicity effectsof pesticides in both animal and human health. There wasmisinterpretation among the farmers where pesticides wereregarded as drugs rather than toxic compound to increaseproductivity. The organochlorines/OCs (lindane and heptachlor)were common pesticide contaminants found in soils of 7.9-11.4 ppb, but no organophospates (OPs) were detected. BothOCs and OPs were also detected in soils of Lembang at a rangeof 11.53-65.63 ppb and 0.6-2.6 ppb, respectively. There werepesticide residues detected in weeds collected from Pangalengan(8.93 ppb lindane, 2.05 ppb heptachlor, and 33.27 ppbchlorpyriphos methyl/CPM and Lembang (6.45 ppb lindane,2.65 ppb endosulfan, 6.85 ppb diazinon, and 0.5 ppb CPM).Only endosulfan with least residue level (0.1 ppb) was detectedin organic cabbages, whereas lindane was detected much higher(3.7 ppb) in non-organic cabbages. Pesticide residues were notdetected in milk of dairy cattle fed on by-products of organiccabbages, but lindane was still present in milk of dairy cattle fedon non-organic cabbages for 7 days subsequently. The presentstudy indicates that the organic farming practice may reducepesticide residues in animal and agricultural products. Farmersappreciated that pesticides may cause residual effects on theirproducts (95.2%) and affected public health and environment(92.9%). Therefore, they were willing to convert theiragricultural practices to organic farming (69.1%).